Implementation of Green Accounting on Company Performance from Maqashid Syariah Index - Evi Eka Wati; Mohd Shahril Ahmad Razimi; Ersi Sisdianto; Lutfia Aprilian (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2022)
The use of the Islamic Syariah Index is a parameter in measuring company performance as a reflection that companies listed on the Indonesian Syariah Stock Index (ISSI) have carried out operational activities in accordance with Syariah objectives, i.e. the virtues of the people. The performance of Maqashid Syariah Index can be analyzed from several factors that influence it, among others green accounting. This study aims to examine the effect of the application of green accounting on the company's performance from Maqashid Syariah Index. This research uses quantitative research. The population in this study is mining companies listed on the Indonesian Syariah Stock Index (ISSI) from 2016-to 2020. The sampling technique of this study is a purposive sampling technique. The number of companies becoming samples are 10. The type of data used is secondary data in the form of financial and annual reports obtained from the official website of the Indonesia Stock Exchange and the companies website. The dependent variable used in this study is the Maqashid Syariah Performance Index. Meanwhile, the independent variable is green accounting. The data analysis method used is simple regression analysis with the help of the E-Views 10. This research demonstrates that green accounting variable has a positive and.